Emotion Regulation and Empathy: Which Relation with Social Conduct?. Issue 2 (4th March 2018) - Laghi, Fiorenzo; Lonigro, Antonia; Pallini, Susanna; Baiocco, Roberto
ABSTRACT: A shared consensus among researchers deals with the positive association between the ability to effectively regulate and manage one's emotion and the engagement in empathic behavior and morally desirable actions. This study was designed to investigate how dispositional reliance on suppression and reappraisal differently impacted on the cognitive and affective components of empathy and on social conduct, distinguishing among prosocial, internalizing, and externalizing behaviors. Two hundred nineteen middle adolescents were enrolled and fulfilled self-reports assessing emotion regulation strategies, empathy, and social behaviors. The results suggest that there are important distinctions among the emotion regulation strategies and the components of empathy as they relate to one another and to prosocial behavior and problem conduct. Specifically, cognitive reappraisal was related to prosocial behavior through empathic concern. While internalizing behavior was associated with emotion regulation strategies, externalizing behavior was only related to perspective-taking ability. Delimitations and practical implications were discussed.